PENGARUH POLA ASUH ORANGTUA PADA PERKEMBANGAN SOSIAL EMOSIONAL ANAK - Septiani, Dwi Septiani; Yusuf Siregar, Muhammad; Masthura Azis, Ainul; Ananda, Chofifah Khairi (Cv Arsy Persada Quality, 2022)
Parents are the first educators for their children who have the obligation to guide, protect and raise children. Its existence is very important, so that the role of parents becomes the basis in the formation of the child's personality and has an influence on socio-emotional development. This effort can be realized, if parents apply the right parenting style, because parenting affects this development. For this reason, it is necessary to have a better understanding of parents' social-emotional development of children, so that children's social-emotional development develops well and is accepted in the community. The method used is the library method. The results of this discussion indicate that in raising children, parents have different opinions in educating children. There are 3 types of parenting, namely democratic, authoritarian and permissive. These three parenting styles have different impacts on children's socio-emotional development. Where democratic parenting has many positive impacts, while authoritarian and permissive parenting has many negative impacts. For this reason, it is recommended that parents apply this